The normatively relativised logical argument from evil - Bishop, John (International journal for philosophy of religion, 2011)
It is widely agreed that the ‘Logical’ Argument from Evil (LAFE) is bankrupt. We aim to rehabilitate the LAFE, in the form of what we call the Normatively Relativised Logical Argument from Evil (NRLAFE). There are many different versions of a NRLAFE. We aim to show that one version, what we call the ‘right relationship’ NRLAFE, poses a significant threat to personal-omniGod-theism—understood as requiring the belief that there is an omnipotent, omniscient, perfectly good person who has created our world—because it appeals to value commitments theists themselves are likely to endorse. The ultimate success of this NRLAFE will rest on developing a theological ethics of right relationship that rejects as morally flawed the exercise of omnipotence first to sustain horrors and then to redeem them. Yet a vindicated NRLAFE of this sort need not require atheism, but only rejection of the standard conception of God as a personal omniGod.